Pembinaan Kedisiplinan Santri Secara Humanistik di Pondok Pesantren An-Nur - Alfi Mardiansyah; Dzulfikar Akbar Romadlon (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
The purpose of discipline research in pesantren is to maintain discipline at all times so that students do not commit or repeat offenses. Therefore, the way to create awareness of santri discipline can be achieved through humanistic education, namely always fostering good behavior and mutual respect between fellow human beings. Humanistic coaching of santri discipline in An-nur Islamic boarding school through environmental arrangements that support santri discipline such as mosques, dormitories and schools. Furthermore, the child-friendly boarding school program uses logical consequences so that there is no cruel punishment system, no more corporal punishment or the like on students. This type of research uses field research using descriptive qualitative methods. The data collection uses observation, interviews, and documentation. The data generated from interviews and observations were then analyzed qualitatively. Qualitative analysis is carried out to understand the meaning of the data obtained. This research is expected to contribute to improving the quality of student discipline coaching at An-Nur Islamic Boarding School and other boarding schools